"I Am a Parrot": Literacy Ideologies and Rote Learning. (June 2022) - Bhattacharya, Usree
Widely prevalent in a variety of educational contexts around the world, rote learning practices entail repetition techniques to acquire new knowledge. These practices have long been critiqued because of the emphasis on recall rather than deep understanding. Less attention has been directed, however, at the literacy ideologies underpinning such practices: specifically, how such practices shape what students perceive as learning and how they see themselves as learners. In order to examine this, I draw on data from an 8-year investigation into the language and literacy socialization of six young boys who lived at an orphanage and attended a village school in suburban New Delhi. In addition to uncovering ideologies related to rote learning practices, I show how students acted as "bad subjects" by discursively resisting socialization into passive learner subjectivities. The findings are then related to the reproduction of inequality within the educational system through literacy practices.